2021
DOI: 10.3390/ani11072152
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Estrogens Present in Environment on Health and Welfare of Animals

Abstract: Nowadays, there is a growing interest in environmental pollution; however, knowledge about this aspect is growing at an insufficient pace. There are many potential sources of environmental contamination, including sex hormones—especially estrogens. The analyzed literature shows that estrone (E1), estradiol (E2), estriol (E3), and synthetic ethinyloestradiol (EE2) are the most significant in terms of environmental impact. Potential sources of contamination are, among others, livestock farms, slaughterhouses, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 138 publications
0
19
0
Order By: Relevance
“…Additionally in fish, estrogen regulates behaviour patterns such as territorial aggression [29] and changes in immune responses [31] , [30] . Wojnarowski et al [32] reported similar effects of estrogen on mammals in addition to disturbances in the regulation of both proapoptotic and anti-apoptotic processes, as well as the occurrence of neoplastic processes causing a drastic decrease in animal welfare. In mammals, elevated levels of estrogens are linked to reproductive disorders [33] , [34] and increased risk of carcinogenesis [36] , [21] , [35] , [37] .…”
Section: Introductionmentioning
confidence: 97%
“…Additionally in fish, estrogen regulates behaviour patterns such as territorial aggression [29] and changes in immune responses [31] , [30] . Wojnarowski et al [32] reported similar effects of estrogen on mammals in addition to disturbances in the regulation of both proapoptotic and anti-apoptotic processes, as well as the occurrence of neoplastic processes causing a drastic decrease in animal welfare. In mammals, elevated levels of estrogens are linked to reproductive disorders [33] , [34] and increased risk of carcinogenesis [36] , [21] , [35] , [37] .…”
Section: Introductionmentioning
confidence: 97%
“…The Vaal River drains most of the wastewater from the metropolitan City of Johannesburg and has been termed one of Africa's workhorse. Presence of these contraceptives in aquatic ecosystems has been linked with diverse negative effects that include intersex organisms [25,26], abnormal secondary sex characteristics [27][28][29], reduced fecundity [30] and changes in population sex ratios [31]. Most of these effects have dire consequences on the populations of the affected organisms.…”
Section: Pharmaceuticalsmentioning
confidence: 99%
“…The biological basis of the aggression mechanism in the case of a domestic dog is still not fully understood, but there are many indications that hormones such as testosterone, estrone, or serotonin may play a role in it [96][97][98], As indicated in the available literature, in many cases the blame for the aggressive behavior of both male and female dogs is the sex hormones found naturally in their bodies [99]. In such a case, it is often recommended to castrate or sterilize aggressive individuals in order to reduce the existing level of aggression or other behaviors perceived as negative by the owners [100,101].…”
Section: Hormones and Aggressive Behaviormentioning
confidence: 99%
“…As performed studies show, the percentage of sterilized or castrated dogs is still growing, reaching almost 80-90% in many developed countries [102,103]. These treatments can bring many health benefits in terms of individuals and well-being for the population, but an increasing number of researchers indicate that lowering the level of sex hormones does not significantly reduce the number of negative behaviors or the level of individual aggression In the case of males, masculinization of the brain takes place during fetal life, and lowering testosterone levels in an adult or adolescent individual may not weaken these behaviors as evidenced by studies performed by McGreevy et al [98]. Similar observations regarding the spaying procedure on females were presented by Starling et al [99].…”
Section: Hormones and Aggressive Behaviormentioning
confidence: 99%